Comparative analysis of virulence determinants, antibiotic susceptibility patterns and serogrouping of atypical enteropathogenicEscherichia coliversus typical enteropathogenicE. coliin India. Issue 10 (October 2015) - Malvi, Supriya; Appannanavar, Suma; Mohan, Balvinder; Kaur, Harsimran; Gautam, Neha; Bharti, Bhavneet; Kumar, Yashwant; Taneja, Neelam
Abstract : N/A: The epidemiology of enteropathogenic Escherichia coli (EPEC) and the significance of isolation of atypical EPEC (aEPEC) in childhood diarrhoea have not been well studied in an Indian context. A comparative study was undertaken to investigate virulence determinants, antibiotic susceptibility patterns and serogrouping of typical EPEC (tEPEC) versus aEPEC causing diarrhoea in children. A total of 400 prospective and 500 retrospective E. coli isolates were included. PCR was performed for eae, bfpA, efa, nleB, nleE, cdt, ehxA and paa genes. The Clinical and Laboratory Standards Institute's disc diffusion test was used to determine the antimicrobial susceptibility. Phenotypic screening of extended spectrum β‐lactamases (ESBLs), AmpC and Klebsiella pneumoniae carbapenemase (KPC) production, and molecular detection of bla NDM‐1, bla VIM, bla CTX‐M‐15, bla IMP and bla KPC were performed. aEPEC (57.6 %) were more common as compared with tEPEC (42.3 %). The occurrence of virulence genes was observed to be three times higher in aEPEC as compared with tEPEC, efa1 (14.7 % of aEPEC, 4 % of tEPEC) being the most common. Most of the isolates did not belong to the classical EPEC O‐serogroups. The highest resistance was observed against amoxicillin (93.22 %) followed by quinolones (83 %), cephalosporins (37.28 %), cotrimoxazole (35.59 %) and carbapenems (30.5 %). Overall equal numbers of aEPEC (41.17 %) and tEPEC (40 %) were observed to be multidrug‐resistant. Fifteen EPEC strains demonstrated presence of ESBLs, five produced AmpC and four each produced metallo‐β‐lactamases and KPC‐type carbapenemases; eight, seven and one isolate(s) each were positive for bla VIM, bla CTX‐M‐15 and bla NDM‐1, respectively. Here, to the best of our knowledge, we report for the first time on carbapenem resistance and the presence of bla NDM‐1 and bla CTX‐M‐15 in EPEC isolates from India.